THE EFFECT OF EMOTIONAL INTELLIGENCE, MANAGEMENT ACHIEVEMENT KNOWLEDGE AND MOTIVATION ON ADMINISTRATIVE OFFICIAL CREATIVITY: Leadership - Enadarlita; Mukhtar; Risnita (PT. Berkah Digital Teknologi, 2022)
This study aims to see and discuss the direct and indirect effects between variables of emotional intelligence, knowledge management and achievement motivation on the creativity of government agency administrators in Jambi Province, either partially or simultaneously. The research was conducted using a quantitative research method with a survey method carried out in district/city governments in Jambi Province. The unit of analysis is administrator officials who have attended level III leadership education and training in Jambi Province, a population of 601 people and the sample in this study was determined by the total sampling technique considering the number of respondents from the three regions was only 126 people. The hypotheses in this study are: emotional intelligence, knowledge management and achievement motivation have a direct and indirect positive effect either partially or simultaneously on the creativity of administrator officials. Hypothesis testing using path analysis, with a significance level of 5 percent alpha (α = 0.05). This study concludes: that overall there is a positive and significant influence between the variables of emotional intelligence, knowledge management and achievement motivation on the creativity of administrator officials, either partially or simultaneously. The implication of this research is that it is something beyond which is not revealed in this study but can make a better contribution to increasing creativity. In the creativity variable, researchers found indicators of managing change and commitment to change. In the variable of emotional intelligence found indicators of self-development, self-development of others, self-control and patient and tenacious attitudes can increase creativity. In the knowledge management variable found indicators of conflict management, performance management and decision making can increase creativity. Meanwhile, the achievement motivation variable was found to build integrity, strong determination and result orientation to increase creativity.